2007
DOI: 10.1021/ct700051j
|View full text |Cite
|
Sign up to set email alerts
|

Stabilities and Spin Distributions of Benzannulated Benzyl Radicals

Abstract: The effects have been studied of mono- and dibenzannulation of a benzyl radical with hybrid density functional theory (B3LYP) and quadratic configuration interaction theory (QCISD). Bond dissociation energies and enthalpies are reported that were determined at the common level QCISD/6-311G**//B3LYP/6-31G* for the benzylic C-H bonds of toluene 1H, the monobenzannulated polycyclic aromatic hydrocarbons (PAH) 1- and 2-methylnaphthalene 2H and 3H, the dibenzannulated PAHs 9-methylanthracene 4H and 9-methylphenanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…This differential enhancement in the rotational energy barriers implies that the allyl radical is able to utilize the π-conjugation more effectively for radical delocalization, in turn increasing the rotational barrier by 4.6 kcal/mol. This result is similar to the findings of Sui et al, who investigated the spin distributions of benzannulated benzyl radicals . On the contrary, the benzyl radical is not able to utilize the extended conjugation effectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This differential enhancement in the rotational energy barriers implies that the allyl radical is able to utilize the π-conjugation more effectively for radical delocalization, in turn increasing the rotational barrier by 4.6 kcal/mol. This result is similar to the findings of Sui et al, who investigated the spin distributions of benzannulated benzyl radicals . On the contrary, the benzyl radical is not able to utilize the extended conjugation effectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear for the benzyl radical that utilization of the phenyl and allyl units is minimal, highlighting our original claim that benzyl carbons are much less likely to benefit from conjugation from an energetic or rotational barrier perspective. This perspective on radical delocalization is shared by Sui et al, who suggested that spin density distributions onto annulated arenes is avoided as much as possible . Interestingly, the degree of spin delocalization on the benzene ring in 2A is in quantitative agreement with the populations in 2B , further indication that benzyl radicals do not utilize the aromatic unit to a greater extent than with compound 2A .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From what is known computationally of benzyl radicals,30 extension of the conjugated systems to naphthyl groups makes radical delocalization less efficient, and the calculated BDEs of 1‐naphthyl and 2‐naphthyl CH bonds are higher than those of benzylic CH bonds by about 1 kcal mol −1 . This is reflected in the poor selectivity observed (Table 1, entries 5 and 6) and led us to investigate the influence of BDE on oxidation selectivity.…”
Section: Resultsmentioning
confidence: 99%